2017
DOI: 10.3171/2016.7.jns16932
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided endoscopic surgery for spontaneous supratentorial intracerebral hematoma

Abstract: OBJECTIVE Endoscopic removal of intracerebral hematomas is becoming increasingly common, but there is no standard technique. The authors explored the use of a simple image-guided endoscopic method for removal of spontaneous supratentorial hematomas. METHODS Virtual reality technology based on a hospital picture archiving and communications systems (PACS) was used in 3D hematoma visualization and surgical planning. Augmented reality based on an Android smartphone app, Sina neurosurgical assist, allowed a projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…All craniotomy hematoma evacuation surgery followed the principle of minimal invasiveness. Surgery procedures were based on the method described in the previous study 11–13. A CT scan was carried out 24 hours after surgery to evaluate the hematoma evacuation efficiency of the operation.…”
Section: Methodsmentioning
confidence: 99%
“…All craniotomy hematoma evacuation surgery followed the principle of minimal invasiveness. Surgery procedures were based on the method described in the previous study 11–13. A CT scan was carried out 24 hours after surgery to evaluate the hematoma evacuation efficiency of the operation.…”
Section: Methodsmentioning
confidence: 99%
“…With the rapid advancement of imaging software and transparent tube sheath, endoscopic surgery has gradually become an effective and well-accepted method for treating ICH [9][10][11][12][13]. Endoscopic hematoma evacuation has become well received for its high evacuation rate and less complication, especially in patients with moderatesized hematoma [14]. In the present study, we applied endoscopic surgery without DC for patients with large putaminal ICH and assessed the efficacy and safety of this procedure.…”
Section: Introductionmentioning
confidence: 99%
“…4,10,13 We previously reported that endoscopic removal of intracerebral hematomas arising from spontaneous non-vascular malformations achieved satisfactory results. 9 In this study, endoscopic removal of subacute subdural hematomas was performed. The small bone window created in the present study group was slightly larger than that made in burr hole drainage, but a much smaller window was created than that used in common bone flap craniotomy in control group.…”
Section: Discussionmentioning
confidence: 99%